2019
DOI: 10.1520/jte20170547
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Bending Performance of Composite H-Shaped Piles

Abstract: There has been a great increase in the number of structural members composed of two or more materials with different stress–strain distributions. This study investigated the bending performance of composite H-shaped piles subjected to bending moments. Load–displacement hysteresis curves were analyzed using limit state analysis, and eight specimens—six composite H-shaped piles made of reinforced concrete and H-shaped steel beams (i.e., composite H-shaped piles) and two conventional H-shaped steel piles—were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In their study, experiments were conducted on different specimens, such as end reinforced steel plates, steel bars, and reinforced studs. Jeong et al 4 studied the ductility of composite and conventional H-beams. For example, for a composite H-beam composed of an H-beam and glulam 5 , limit state analysis was used to analyze the load–displacement hysteresis curve, and it was found that the ductility of the composite H-beam was 138% higher than that of the conventional H-beam.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, experiments were conducted on different specimens, such as end reinforced steel plates, steel bars, and reinforced studs. Jeong et al 4 studied the ductility of composite and conventional H-beams. For example, for a composite H-beam composed of an H-beam and glulam 5 , limit state analysis was used to analyze the load–displacement hysteresis curve, and it was found that the ductility of the composite H-beam was 138% higher than that of the conventional H-beam.…”
Section: Introductionmentioning
confidence: 99%